Scholars and Hadith Interpretation on the Phenomenon of Spirits in Indonesia - Anggaraini, Yeni; Friyadi, Arif (UIN Syarif Hidayatullah Jakarta, 2025)
The phenomenon of spirits is often discussed in society, especially in Indonesia, which is rich in local culture and beliefs. As part of Islamic teachings, this phenomenon also receives attention from the perspective of hadith and the views of scholars. This paper aims to examine how the scholars' views and interpretations of the hadith related to the phenomena of wandering spirits, as well as its relevance to local beliefs. Using a qualitative approach, the article analyzes the views of scholars who refer to hadith texts both in support of and in response to skepticism about the existence of spirits that roam after death. It also explores the influence of local culture on the interpretation of these traditions and how Indonesian scholars harmonize Islamic teachings with the spiritual practices of the people. The results of the study show that although the traditions related to wandering spirits have a variety of interpretations, scholars tend to prioritize the principles of Islamic teachings that emphasize the importance of the afterlife and reject beliefs that are not based on sound Islamic law. The findings provide further insight into the relationship between religious teachings and local culture, as well as the contribution of ulema in safeguarding the faith of the people through proper understanding of the traditions.